2016
DOI: 10.3390/en9090680
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Index Decomposition of Energy-Related Carbon Emissions and Their Decoupling from Economic Growth in Northwest China

Abstract: Rapid economic growth in Northwest China has been accompanied by a dramatic increase in carbon emissions. Based on the two-level Logarithmic Mean Divisia Index (LMDI) method, this study decomposes changes in energy-related carbon emissions in Northwest China during 1995-2012 from the regional and provincial perspectives. Further, by constructing an expanded decomposition model of the decoupling index, this paper quantitatively analyzes delinking indicators of economic activity and environmental pressure in Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 73 publications
4
17
0
Order By: Relevance
“…Secondly, studies performed at the regional/provincial level were all resourceful, including those on Northwest China [20], Yunnan [21], Guangdong [22][23][24], Jiangsu [25,26], Shanghai [27], Chongqing [28,29], and Xinjiang [30]. The factors found to have the greatest effect on carbon emissions were economic activity [20], investment [21], energy density [21,23,24,26], economic growth [23,24], export [21], population scale [24], energy efficiency [20], technical progress [24], industrial structure [22,23,26], and energy Sustainability 2019, 11,7008 3 of 20 mix [24,26]. For example, Dong et al [21] analyzed the energy-related carbon emissions of five provinces in Northwest China from 1995 to 2012 (Shaanxi, Ningxia, Qinghai, Gansu, and Xinjiang) and found that the effect of economic activity produced a significant impact on increased carbon emission.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, studies performed at the regional/provincial level were all resourceful, including those on Northwest China [20], Yunnan [21], Guangdong [22][23][24], Jiangsu [25,26], Shanghai [27], Chongqing [28,29], and Xinjiang [30]. The factors found to have the greatest effect on carbon emissions were economic activity [20], investment [21], energy density [21,23,24,26], economic growth [23,24], export [21], population scale [24], energy efficiency [20], technical progress [24], industrial structure [22,23,26], and energy Sustainability 2019, 11,7008 3 of 20 mix [24,26]. For example, Dong et al [21] analyzed the energy-related carbon emissions of five provinces in Northwest China from 1995 to 2012 (Shaanxi, Ningxia, Qinghai, Gansu, and Xinjiang) and found that the effect of economic activity produced a significant impact on increased carbon emission.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior to 1977, energy density produced a positive effect on carbon emissions but after 1978, it produced an inhibitory effect [30]. In terms of decoupling effect analysis, Dong et al [20] pointed out that in the five northwestern provinces, a strong decoupling effect was only seen from 2007 to 2009, and the rapid economic growth of the five northwestern provinces posed a serious threat to the decoupling process [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, Xinjiang Uygur Autonomous region, the biggest province in China (Fig. 1), has surging energy consumption demands and carbon emissions in the transport sector [7]. In 2013 the "One Belt, One Road" initiative was put forward by China's government [8][9].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the stock explanatory limitation of the LMDI method could be eliminated [52]. On the other hand, by combining index decomposition results and the decoupling index (especially the decoupling effort index), we can identify which factors and to what extent enhance or curtail carbon emissions [7,52,53].…”
Section: Introductionmentioning
confidence: 99%
“…Among various index decomposition analysis methods of the IDA model, logarithmic mean Divisia index method was considered the most suitable and widely applied [48,49]. In addition, studies on decoupling tended to focus more on the exploration of the link between human economic activities and environmental changes [50][51][52], using Tapio method [53].…”
Section: Introductionmentioning
confidence: 99%